Value Pluralism and the Challenge of Normativity in the Zhuangzi - Mark L. Farrugia (Journal of World Philosophies, 2017)
Kim-chong Chong’s 2016 book on the Zhuangzi balances the textual and historical approaches with conceptual and contemporary philosophical concerns. The focus on the early Confucian context and the philosophy of value pluralism, as well as the analysis of key concepts and creative interpretation of well-known passages, mark out Chong’s Zhuangzi from other accounts. Nevertheless, Chong faces the interpretative and philosophical challenge of reconciling value pluralism with the normative concerns and privileged ideals also present in the Zhuangzi.